Care in the last hours to days of life. (December 2022) - Harris, Dylan
Abstract: Care of the dying is a fundamental part of a clinician's role. When somebody is dying, rather than there being 'nothing more that can be done', there is a lot to consider and explore to support and facilitate a 'good death'. Key aspects of end-of-life care should incorporate the following (TERMINAL): a Team diagnosis of dying; Exploring the dying person's priorities and preferences (e.g. what is important to them, religious or spiritual wishes or beliefs); Resuscitation (and the role of a Do Not Attempt Resuscitation (DNAR) form); Medicines and monitoring (review oral medication, use of a subcutaneous infusion for essential medication, rationalization of observations and blood tests); Involving those important to the person (and exploring their needs and concerns); Nutrition and hydration; Anticipatory prescribing (the 'four As': analgesic, anxiolytic, anti-secretory, antiemetic); and Location (how high a priority is place of death for this person?). Communication, and communication skills, are critically important in end-of-life care, and the uncertainty around diagnosing dying can be conveyed by explaining that you are concerned that the person is now 'sick enough to die' in the next hours to days.